Konsep Bahan Ajar dalam Al-Qur'an: Kajian Kitab Tafsir Al-Misbah dan Tafsir Ibnu Katsir dalam Pendidikan Islam - Alfiyah, Avif; Azizah, Shofiqotun; Avif Alfiyah (Jawa Timur: Prodi. Ilmu Al Quran dan Tafsir Fakultas Ushuluddin IAI Tarbiyatut Tholabah, 2024)
The concept of teaching materials in the Qur'an plays a significant role in Islamic education, both in providing spiritual guidance and educating humans to think critically and act according to the principles of justice, truth, and virtue. This study aims to explore the concept of teaching materials in the Qur'an, focusing on the values contained in the tafsir works of al-Mishbah and Ibnu Katsir and their application in educational contexts. The research employs a qualitative approach using the tafsir muqaran (comparative) method, which compares the interpretations of Qur'anic verses by scholars to gain a comprehensive understanding. The findings reveal that the Qur'an encompasses three primary educational values: (1) I’tiqodiyah Values (faith education), which include strengthening faith in Allah along with His names and attributes; (2) Khuluqiyah Values (moral education), exemplified by the Prophet Muhammad in educating his companions; and (3) Amaliyah Values (behavioral education), emphasizing the importance of practicing the knowledge acquired. These findings demonstrate that the Qur'an is not only a rich source of teaching materials but also relevant in fostering integration between religious and modern knowledge. This study contributes to the development of Qur'an-based teaching materials that are practical and capable of shaping morally upright and intellectually advanced generations.